Improved CO2 adsorption capacity and cyclic stability of CaO sorbents incorporated with MgO - Mohd Daud, Farah Diana; Vignesh, Kumaravel; Sreekantan, Srimala; Mohamed, Abd. Rahman (Royal Society of Chemistry, 2015)
Calcium oxide (CaO) sorbents incorporated with magnesium oxide (MgO) were synthesized using a co-precipitation route. The sorbents were prepared with different MgO concentrations (from 5 wt% to 30 wt%). The as-prepared sorbents were characterized using X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), energy dispersive X-ray spectroscopy (EDX) and BET surface area analysis techniques. The sintering effect of CaO sorbents was decreased after the incorporation of MgO. The sorbents with 5 wt% and 10 wt% of MgO retained their CO2 adsorption capacity over multiple cycles. Most importantly, CaO with 10 wt% MgO showed constant CO2 adsorption capacity over 30 carbonation cycles. The results revealed that CaO with 10 wt% MgO is sufficient to produce sorbents with high surface area, good structural stability and enhanced CO2 adsorption capacity.